Integrasi Bahan Ajar Berbasis Kearifan Lokal Kajang dalam Meningkatkan Keterampilan Berpikir Kritis - Ramadani, Iqra (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
Challenges in globalization highlight the need to integrate education, local wisdom, and environmental sustainability. Local wisdom-based education bridges science and culture, fostering critical thinking skills vital for global challenges. This research examines how teaching materials based on the local wisdom of the Kajang Ammatoa indigenous community can play a role in developing students' critical thinking skills. Literature review and field observation were used to identify potential local wisdom values of Kajang Ammatoa, such as Pasang ri Kajang, traditional rituals, and plant conservation, which were integrated into teaching modules, LKPD, and Digital Storytelling. The results of the analysis show that local wisdom-based teaching materials can be a bridge between science and culture, enriching students' scientific understanding through cultural contexts relevant to everyday life. In addition, this learning enhances students' critical thinking skills through multidisciplinary analysis that includes natural science and local cultural practices. This research also found that the integration of local wisdom in science learning can directly support in facing the challenges of the times in the era of globalization, such as quality education, handling climate change, and environmental preservation. Therefore, local wisdom-based teaching materials should be considered as an effective strategy in achieving a more holistic and sustainable education.